Frequency of Winter Coupled North Pacific/North America Circulation Regimes - James E. Overland; Muyin Wang (Climate, 2022)
The jet stream over North America alternates between a more zonal direction and a wavy pattern (a more meridional flow) associated with persistent blocking patterns. To better understand these important patterns, we base our study on the frequency of winter (November–February) events during 1981–2020, based on four circulation regime types: blocking, the Alaskan Ridge, North American Ridge/Pacific Wave-Train; and zonal, the Pacific Trough and the central Pacific High/Arctic Low (Amini and Straus 2019). Increased information on within and between season variability is important, as the impacts of blocking include the California heatwave and mid-continent or east coast cold spells. Rather than extensive pattern duration or significant trends, temporal variability is the major feature. In some years the combination of the Alaskan Ridge and North American Ridge/Pacific Wave-Train patterns represent ~5 major events covering 35 days of the 120-day winter period, with individual events lasting 10 days. Within-season multiple occurrences and short durations dominate the winter meteorology of the continental United States. The characterization of the persistence of these blocking events is relevant for extended range forecasts.